(untitled) (International Journal of Engineering Management Science, 2018)
The tribological behavior of 3D-printed polymer composites reinforced with graphite particles, fabricated using the Fused Deposition Modeling (FDM) process, is investigated in this study. Acrylonitrile Butadiene Styrene (ABS) was used as the base polymer, and graphite particles were incorporated at 5wt% and 10wt% concentrations to enhance its tribological properties. The composites were extruded into filaments and 3D-printed using a standard FDM printer. Tribological tests were conducted under varying loads (10 N, 20 N, and 30 N) and speeds (0.1 m/s, 0.2 m/s, and 0.3 m/s) to evaluate the friction and wear characteristics of the composites. The results indicate that the addition of graphite significantly improves the wear resistance and reduces the coefficient of friction, with the 10wt% graphite composite showing the most promising performance. This study highlights the potential of graphite-reinforced ABS composites for applications requiring enhanced tribological properties, such as automotive components, bearings, and sliding parts.